Brief review of Ghana’s food system transformation pathways - Asante, Felix A. (International Food Policy Research Institute, 2024)
Global estimates show over half a billion people go hungry (FAO, 2020) and close to 2 billion people are either obese or overweight with another 2 billion of the world’s population suffering from micronutrient deficiencies (Micha et al., 2020, Fresco et al., 2017). Inarguably, the world faces significant malnutrition problem (including micro- and macro-nutrient deficiencies, obesity, and diet related non-communicable diseases). This is evident in a recent analysis pointing out that effort in achieving the Global Nutrition Targets is likely to be missed. The observed malnutrition threat is accompanied by climate change, which is influencing food production and consumption trends, and thereby leading to undernutrition and affecting overall development. In addition, there are growing incomes, accelerated urbanization, and expanding middle classes which are also causing significant changes in consumer behaviour and nutritional choices, necessitating both public and private expenditures for better food market integration. As a result, there is a pressing need to examine our food systems to guarantee food and nutrition security and to advance sustainable development. It is likely that the COVID-19 impact may further exacerbates the worsening food insecurity and nutritional status of the most vulnerable groups including women, children and adolescents, refugees and displaced people, smallholders in rural areas, and the urban poor.